The Water Quality Index of Springs in Bauro Village, Timor-Leste - Juvencio Dos Santos,; Listyani R.A., T.; Ev. Budiadi, (ReTII, 2025)
The spring in Bauro Village, Timor-Leste, is used to meet the community's daily needs; therefore, an evaluation is needed to determine the quality of the groundwater from this spring. This research aims to assess groundwater quality, particularly using the Water Quality Index (WQI). Evaluation was carried out on 12 springs that emerged from limestone and sandstone. The research results show that not all springs meet the quality standards for drinking water or clean water. The WQI assessment shows that the majority of the 12 sampled sites (S1–S10 and S12) fall into the unsuitable category, indicating high levels of contamination from both natural and anthropogenic sources. Only Bauro spring S11 exhibited excellent water quality, while Luarai spring S12 showed poor drinking water quality and was unsuitable for clean water, reflecting localized contamination and possible mineral enrichment.